Excellent mechanical properties of a novel double-diagonal reinforced mechanical metamaterial with tunable Poisson’s ratios inspired by deep-sea glass sponges - Hongbo Zhang; Yuan Li; Zhiqian Lin; Zhen Zhang; Dayong Hu; Zhenyu Yang (Materials & Design)
In the realm of mechanical metamaterials, those exhibiting high strength and tunable properties were pivotal for advancing smart functionality applications. Inspired by the robust structure of deep-sea glass sponges, the double-diagonal reinforced metamaterial had been recognized for its exceptional mechanical properties. Here, this approach was refined by addressing a previously overlooked aspect, the thickness ratio of diagonal to square struts, and introduced a novel mechanical metamaterial. This innovation enabled the metamaterial to exhibit three distinct deformation patterns, facilitating a transition between negative, zero, and positive Poisson’s ratios, thereby achieving both high strength and sign-switchable Poisson’s ratio characteristics. Through a combination of experimental and numerical analyses, the regulatory mechanism was unraveled by which diagonal reinforcement influenced the metamaterial’s deformation behavior, energy absorption capacity, and Poisson’s ratio, culminating in the development of a programmable mechanical metamaterial. Theoretical investigations were conducted for both the elastic and plastic behaviors of the metamaterial, thoroughly examining the effects of geometric parameters on its mechanical performance. Moreover, compared with traditional diagonal-reinforced metamaterials, this design strategy demonstrated superior mechanical advantages. This comprehensive analysis not only highlighted the functional attributes of the bionic sponge metamaterial but also provided deeper insights into the mechanical mechanisms underlying diagonal reinforcement in metamaterials.